2021
DOI: 10.3389/fmars.2021.666653
|View full text |Cite
|
Sign up to set email alerts
|

On Using Lagrangian Drift Simulations to Aid Interpretation of in situ Monitoring Data

Abstract: One key challenge of marine monitoring programs is to reasonably combine information from different in situ observations spread in space and time. In that context, we suggest the use of Lagrangian transport simulations extending both forward and backward in time to identify the movements of water bodies from the time they were observed to the time of their synopsis. We present examples of how synoptic maps of salinity generated by this method support the identification and tracing of river plumes in coastal re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 45 publications
(62 reference statements)
1
3
0
Order By: Relevance
“…For the surface sample near Arendal, the salinity was lower (30 psu) than the deeper and surrounding samples (33–35 psu), indicating that this water mass might have originated from the Kattegat (Aure et al, 1998 ; Kristiansen & Aas, 2015 ). This is supported by a surface drift model 1 (Callies et al, 2021 ) showing that the water mass originated from the eastern Skagerrak during HE586, while the currents were different during AL557 (Fig. S40 ).…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…For the surface sample near Arendal, the salinity was lower (30 psu) than the deeper and surrounding samples (33–35 psu), indicating that this water mass might have originated from the Kattegat (Aure et al, 1998 ; Kristiansen & Aas, 2015 ). This is supported by a surface drift model 1 (Callies et al, 2021 ) showing that the water mass originated from the eastern Skagerrak during HE586, while the currents were different during AL557 (Fig. S40 ).…”
Section: Discussionsupporting
confidence: 56%
“…In contrast, for AL557 st.4, the surface drift model 1 (Fig. S39 ; Callies et al, 2021 ) showed that the water mass has been moving in the region due to tidal activity but might have originated from the Eider or Elbe estuary. This would be supported by the low salinity of this sample (Fig.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The data are made available in near real time via the COSYNA (Coastal Observing System for Northern and Arctic Seas) data portal (Baschek et al 2017;Breitbach et al 2016). The PELETS-2D code (Callies et al 2021) is used to compute model trajectories for each FerryBox transect. These model trajectories consist of the measured water bodies' positions up to ten days before and after the actual measurement as simulated by the numeric model.…”
Section: Automatic Anomaly Detectionmentioning
confidence: 99%